Donors and Recipients of Living Kidney Donation: A Qualitative Metasummary of Their Experiences - Deborah Ummel; Marie Achille; Jessina Mekkelholt (Journal of Transplantation)
With the notable growth in the qualitative investigation of living kidney donation, there is value in aggregating results from this body of research to learn from accumulated experience. The present paper aims to draw a complete portrait of living donors' and recipients' experience of donation by metasummarizing published studies. We found that donors' experience, particularly the decision-making process, has been more extensively studied than the recipients' perspective. Donors differ in their initial level of motivation to donate but on the whole report positive experiences and personal benefits. They also identify difficult periods and the need for additional resources. Recipients report an often positive but more ambivalent reaction to donation. In terms of relational issues between dyads, while the topic remains understudied, the donor-recipient relationship and gift reciprocity have received the most attention. Results are discussed in terms of their implications for future practice and research.